2010
DOI: 10.1002/ijc.25153
|View full text |Cite
|
Sign up to set email alerts
|

Cancer incidence in people with AIDS in Italy

Abstract: Lo studio è stato condotto in collaborazione con medici, epidemiologi e ricercatori in tutta Italia che sono entrati a far parte del Cancer and AIDS Registries Linkage Study. Tale stuudio ha prodotto una pubblicazione a stampa in cui compare tra gli autori la dr Rosa Maria Limina, di questa Università, che ha inserito questo prodotto con il codice 31053 nella tipologia Articolo su Rivista

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 30 publications
2
72
0
Order By: Relevance
“…However, other factors also appear to be related to the increased incidence of lung cancer in these patients because the risk remains high even after correcting for smoking status [10]. Although some studies do not show a statistically significant increase in the risk of developing lung cancer after HAART [10,20], our study found a doubling of the pre-HAART era risk in the post-HAART era (RR: 2.19, 95% CI: 1.54-3.11), and this result is similar to what was found by Polesel et al in 2010 (RR: 1.8, 95% CI: 1.00-3.2) [21]. The increased risk may be explained in part by the long period from the acquisition of HIV until the diagnosis for lung cancer (11 years on average in the post-HAART era).…”
Section: Lung Cancersupporting
confidence: 90%
“…However, other factors also appear to be related to the increased incidence of lung cancer in these patients because the risk remains high even after correcting for smoking status [10]. Although some studies do not show a statistically significant increase in the risk of developing lung cancer after HAART [10,20], our study found a doubling of the pre-HAART era risk in the post-HAART era (RR: 2.19, 95% CI: 1.54-3.11), and this result is similar to what was found by Polesel et al in 2010 (RR: 1.8, 95% CI: 1.00-3.2) [21]. The increased risk may be explained in part by the long period from the acquisition of HIV until the diagnosis for lung cancer (11 years on average in the post-HAART era).…”
Section: Lung Cancersupporting
confidence: 90%
“…Earlier studies had limited follow-up experience during the ART era, but numerous subsequent studies have suggested that lung cancer risk has increased during the ART era (23,26,30,31,41,53). Few of these studies took age into account, and ART era differences in rates in a large Italian study were obviated after age adjustment (27). ART use at the individual level, rather than ART era, should improve CD4 cell counts and suppress HIV RNA levels but has yielded inconsistent associations with lung cancer risk.…”
Section: Role Of Immunosuppression Hiv Viral Load and Artmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Since the advent of potent combination antiretroviral therapy (cART), which suppresses the replication of HIV-1 and gradually restores immune function, the incidence of non-Hodgkin lymphoma and other AIDS-defining cancers has declined substantially. 7,8,15 In contrast, the incidence of HL, a non-AIDS-defining cancer, does not appear to have decreased, [16][17][18][19] with some studies finding that the incidence may have increased. [8][9][10][11][20][21][22] There is debate on the relationship between immunodeficiency and the risk of HL in HIV-1-infected patients.…”
Section: Introductionmentioning
confidence: 99%